Analysis of the characteristics of endometrial fluid samples in recurrent pregnancy loss patients based on 16S rRNA gene sequencing technology - Wang, Xiaoping; Ding, Nan; Li, Xiaofeng; Lu, Menghao; Wang, Peili (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionRecurrent pregnancy loss (RPL) is a complex condition with multifactorial causes. This study aimed to characterize the microbial composition of endometrial fluid in RPL patients compared with healthy controls.MethodsA total of 114 participants were recruited from the Second Hospital of Lanzhou University between March and September 2023, including 68 RPL patients and 46 healthy controls. Clinical data and endometrial fluid samples were collected. Microbial DNA was extracted and analyzed using 16S rRNA gene sequencing. Microbial diversity was assessed with QIIME, semi-partial correlation analysis was applied to explore associations between groups, and LEfSe was used to identify differentially abundant taxa.ResultsNo significant differences in alpha diversity indices were found between the groups (p>0.05). However, beta diversity showed significant differences (p<0.05), indicating distinct microbial compositions. At the genus level, Vibrio and Pseudoalteromonas were positively correlated with RPL, suggesting their potential role in the condition. LEfSe analysis further validated our results, highlighting several taxa with significant differences in abundance, indicating microbial imbalances in RPL patients.DiscussionThe study emphasizes the impact of microbial imbalances on reproductive health, potentially aiding in the development of targeted interventions to restore microbial balance and improve pregnancy outcomes in RPL patients.